Protopanaxadiol-Enriched Rice Exerted Antiadipogenic Activity during 3T3-L1 Differentiation and Anti-Inflammatory Activity in 3T3-L1 Adipocytes - Chaiwat Monmai; Jin-Suk Kim; Hyun Bo Sim; Doh-Won Yun; Sung-Dug Oh; Eui-Shik Rha; Jong-Jin Kim; So-Hyeon Baek (MDPI AG, 2023)
Ginseng is a traditional medicine with health benefits for humans. Protopanaxadiol (PPD) is an important bioactive compound found in ginseng. Transgenic rice containing PPD has been generated previously. In the present study, extracts of this transgenic rice were evaluated to assess their antiadipogenic and anti-inflammatory activities. During adipogenesis, cells were treated with transgenic rice seed extracts. The results revealed that the concentrations of the rice seed extracts tested in this study did not affect cell viability at 3 days post-treatment. However, the rice seed extracts significantly reduced the accumulation of lipids in cells and suppressed the activation of CCAAT/enhancer-binding protein α (C/EBPα) and peroxisome proliferator-activated receptor γ (PPARγ), which in turn inhibited the expression of adipogenesis-related mRNAs, such as adiponectin, PPARγ, C/EBPα, sterol regulatory element-binding protein 1, glucose transport member 4, and fatty acid synthase. In adipocytes, the extracts significantly reduced the mRNA expression of inflammation-related factors following LPS treatment. The activation of NF-κB p65 and ERK 1/2 was inhibited in extract-treated adipocytes. Moreover, treatment with extract #8 markedly reduced the cell population of the G2/M phase. Collectively, these results indicate that transgenic rice containing PPD may act as an obesity-reducing and/or -preventing agent.